Analisis Faktor-Faktor yang Mempengaruhi Inflasi di Negara ASEAN - Rambe, Nurul Hidayah; Pratomo, Wahyu Ario; Suhaimi, Syech (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The research uses a quantitative approach with the Vector Error Correction Model as a data analysis method. The short-term and long-term results of this study show that changes in the exchange rate throughout the previous period have a positive but insignificant effect on inflation. Inflation is significantly affected by changes in the unemployment rate from the previous period, which has a positive short-term effect. However, the long-term estimation results show that adjustments to the unemployment rate from the previous era have a negative but insignificant effect on inflation. In the previous era, changes in the money supply level have no effect on inflation but have a negative short-term effect. Changes in oil subsidies during the previous era have a negative short-term effect and significantly affect inflation.